The Relationship Between Psychosocial Factors And Musculoskeletal Disorder Complaints Among Workers At PT. Mekar Berseri Sempurna - Fiki Minyati; Zufra Inayah (Journal Hygeia Public Health, 2026)
Intoduction: Musculoskeletal Disorders (MSDs) are among the most common occupational health problems experienced by industrial workers due to exposure to physical and psychosocial risk factors in the workplace. High job demands, work pressure, mental workload, work relationships, and lack of social support may increase the risk of MSD complaints. PT. Mekar Berseri Sempurna is a seafood processing company where most production activities are still performed manually, placing workers at risk of developing musculoskeletal complaints. Method: This quantitative study employed a cross-sectional design. The study population consisted of 80 workers, with 67 respondents selected using simple random sampling. Psychosocial factors were measured using the Copenhagen Psychosocial Questionnaire (COPSOQ), while MSD complaints were assessed using the Nordic Body Map (NBM). Data were analyzed using univariate analysis and Spearman Rank correlation test. Result and Discussion: Most respondents experienced high psychosocial factors (52.2%), while high MSD complaints were reported by 50.7% of respondents. Spearman Rank analysis showed a p-value of 0.006 with a correlation coefficient (r) of 0.333. Conclusion: There was a significant relationship between psychosocial factors and Musculoskeletal Disorders (MSDs) among workers at PT. Mekar Berseri Sempurna. The correlation was positive with weak strength, indicating that higher psychosocial factors were associated with increased MSD complaints.